Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Wisatawan Di d’Kandang Amazing Farm - Aulia, San San Dika; Manurung, Tarida Marlin Surya; Rainanto, Bambang Hengky (Prodi Pariwisata dan LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This research aims to see the influence of service quality and facilities on tourist satisfaction at D'Kandang Amazing Farm. There will be an increase and decrease in the number of tourist visits to D'Kandang Amazing Farm in 2023. The variables used are the quality of services and facilities and tourist satisfaction. The sample used was 108 respondents, taken from tourists who came to visit D'Kandang Amazing Farm. Sampling was carried out using a random sampling technique so that every tourist had the opportunity to participate in sampling. This research uses a quantitative approach and carries out several tests and analyzes such as descriptive analysis, validity test, reliability test, classical assumption test including normality test, multicollinearity test, heteroscedasticity test and hypothesis test including multiple linear regression analysis, partial test (t test), test simultaneous (f test). This research uses IBM SPSS 25 software to process the data. The results of data processing prove that service quality has a positive effect on tourist satisfaction, facilities have a positive effect on tourist satisfaction and service quality and facilities have a simultaneous effect on tourist satisfaction. Key Words: Sevice Quality, Facilities, Tourist Satisfaction